Expression of ethylene receptor gene LeETR2 in tomato mutant Epi and construction of its antisense expression vector - ZHENG Tie-song; YING Tie-jin; ZENG Guang-wen; HE Guo-qing (浙江大学学报. 农业与生命科学版)
The expressive characteristics of LeETR2 mRNA in tomato mutant Epi and its wild type VFN8 have been studied with RNase protect analysis （RPA） technique. The results showed that LeETR2 mRNA expressed in all the tissues examined, and it's expression was unaffected by the endogenous ethylene in leaves. However, LeETE2 mRNA was developmentally regulated, and partially induced by ethylene in fruits. The results indicated that LeETR2 mRNA exhibits different expression pattern from other ethylene receptor genes in tomato. Moreover, LeETR2 antisense gene expression vector has been constructed for further research.